Teachers’ perspectives on technology-based learning for the kindergarten students - Nur Afifah Rustan; Bambang Yudi Cahyono; Rusdiana Junaid (Intelektual Pustaka Media Utama, 2023)
Ever since the pandemic occured, almost every sector utilize technology to accommodate learning. To tackle every possibility that may interfere the learning process, perspectives in using technology from teachers needed to be taken into account. Thereofore, the needs of finding the perspecives of teachers in teaching and learning especially in kindergarten are crucial since they are still new to the settings. Qualitative research design was applied through Google Form as the media to reach the participants. In collecting the data, the participants were asked about the use of the technology in the teaching and learning process using English as the language of instruction. This research involved eight teachers (T1, T2, T3, T4, T5, T6, T7, T8) of English for young learners in three different schools. Results revealed that there were four main themes which indicated the use of technology in teaching in the kindergarten students, namely: i) Technology motivates children to learn; ii) Technology effects children’s health; iii) Technology is an optional medium; and iv) Suitable application are needed for better learning. These findings can be useful for the present and future stakeholders of kindergarten schools especially in the use of information and communication technology (ICT) in the teaching of English as a foreign language (EFL) at kindergarten settings.